2009
DOI: 10.1073/pnas.0909345106
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic screens identify CINP as a genome maintenance protein

Abstract: The DNA damage response (DDR) has a critical role in maintaining genome integrity and serves as a barrier to tumorigenesis by promoting cell-cycle arrest, DNA repair, and apoptosis. The DDR is activated not only by genotoxic agents that induce DNA damage, but also during aberrant cell-division cycles caused by activated oncogenes and inactivated tumor suppressors. Here we use RNAi and cDNA overexpression screens in human cells to identify genes that, when deregulated, lead to activation of the DDR. The RNAi sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 44 publications
5
61
0
Order By: Relevance
“…pEGFP was purchased from Clontech. pEGFPTopBP1-978-1286 wild type (also referred to as GFP-TopBP1-AAD below), pEGFP-TopBP1-978-1286 W1145R, Myc-TopBP1, and HA-CINP were provided by David Cortez (Vanderbilt University School of Medicine, Nashville, TN) (28,29). Flag-Hus1 and Flag-Rad17 were purchased from Origene.…”
Section: Methodsmentioning
confidence: 99%
“…pEGFP was purchased from Clontech. pEGFPTopBP1-978-1286 wild type (also referred to as GFP-TopBP1-AAD below), pEGFP-TopBP1-978-1286 W1145R, Myc-TopBP1, and HA-CINP were provided by David Cortez (Vanderbilt University School of Medicine, Nashville, TN) (28,29). Flag-Hus1 and Flag-Rad17 were purchased from Origene.…”
Section: Methodsmentioning
confidence: 99%
“…Identifies USP11-We previously used activation of the DNA damage response as a reporter to identify genome maintenance activities in mammalian cells (44). 73 genes were identified that caused increased DDR signaling when silenced by RNAi even in the absence of any added genotoxic agent.…”
Section: Rnai Screen For Parp Inhibitor (Parpi) Hypersensitivitymentioning
confidence: 99%
“…Weak CINP sumoylation has been observed by another group through a screening system, suggesting the existence of other modified types of CINP (44). Interestingly, Lovejoy et al (38) and another group (45) recently identified CINP as a checkpoint protein to maintain genomic stability, thus shedding light on the function of CINP in genomic maintenance and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished Rb expression can also lead to inappropriate DNA synthesis following a senescence trigger (37). Of note, CINP has recently been identified as a genome maintenance protein (38), and it is known that the sensing and repairing of DNA damage are involved in cell cycle progression. Therefore, we theorized that the DNA damage response could be exploited by NS5B to delay cells in S phase.…”
Section: Ns5b/cinp Association Is Responsible For S Phase Delay and Smentioning
confidence: 99%